Frontiers of Business Research in China - Mao, Jiye; Wang, Steven Shuye; Liu, Jun
Frontiers of  Business Research in China (FBR) is a double-blind refereed quarterly journal in business research. FBR offers a multidisciplinary forum for academics, practitioners, and policy makers that focuses on business administration, and encourages interdisciplinary studies and interactions between Chinese and international researchers. FBR publishes original academic and practical research articles that extend, test, or build management theories, as well as contributions to business administration practice, either in the Greater China region or beyond. The Journal also publishes related commentaries and case studies. FBR invites submissions of high-quality manuscripts in all areas of business administration, without limitations on research methods. Major areas of interest include, but are not limited to: Accounting, Finance, Human resources, International business, Marketing, Management information systems, Operations management, Organizational behavior, and Strategic management.